Dynamic diversification history with rate upshifts in Holarctic bell‐flowers (Campanula and allies). (4th February 2017) - Jones, Katy E.; Korotkova, Nadja; Petersen, Jörn; Henning, Tilo; Borsch, Thomas; Kilian, Norbert
Abstract: Campanula s.l . is one of the most speciose flowering plant lineages of the Holarctic (ca. 600 species). In the present study we sequenced three regions of the plastid genome ( petD, rpl16 and trnK / matK ) across a broad sample of Campanula s.l ., which markedly improved phylogenetic resolution and statistical support compared to previous studies. Based on this robust phylogenetic hypothesis we estimated divergence times using BEAST, diversification rate shifts using Bayesian Analysis of Macroevolutionary Mixture (BAMM) and TreePar, and ancestral ranges using Biogeography with Bayesian (and likelihood) Evolutionary Analyses in R . Campanula s.l . is estimated to have originated during the Early Eocene but the major diversification events occurred between the Late Oligocene and Middle Miocene. Two upward diversification rate shifts were revealed by BAMM, specific to the crown nodes of two Campanula clades: CAM17, a mostly South European‐SW Asian lineage originating during the Middle Miocene and containing nearly half of all known Campanula species; and CAM15B, a SW Asian–Sino‐Himalayan lineage of nine species originating in the early Pleistocene. The dynamic diversification history of Campanula and the inferred rate shifts are discussed in a geo‐historical context.